Prevalence of Intimate Partner Violence Victimization and Perpetration Among Youth in Hawai‘i - Baker, Charlene K (University Clinical, Education & Research Associate (UCERA), 2011)
OBJECTIVE: The purpose of the current study was to examine the prevalence of intimate partner violence (IPV) among teens in Hawai‘i. METHODS: Youth from two O‘ahu high schools (N = 623) were asked to complete a quantitative survey about their experiences, as victims and perpetrators, of IPV. RESULTS: The most frequently reported type of violence was monitoring/controlling behaviors. Girls reported higher rates of victimization and perpetration than boys for most violence types. CONCLUSIONS: Future research should examine the contexts in which teen IPV occurs. It will also be important to engage community-based organizations in prevention efforts. Therefore, a train-the-trainer curriculum for IPV prevention and intervention is proposed.